Current issues of pedagogy and psychology - Prokopev N. I., Ananev V. N., Ponomareva L. I., Gurtovoi E. S., Novoselov K. A., Orekhova S. E., Sivak O. A., Shevtsova A. V., Kudriashova S. K., Kudriashov V. I., Gamalienko A. B., Saenko N. V., Piatibratova I. V., Iakusheva O. V., Aleksina T. V., Aleksandrov S. G., Zenkina V. G., Solodkova O. A., Bozhko G. G., Agibalova A. A., Andreeva O. S., Koreneva A. V., Veretennikova N. D., Koreneva A. V., Kalmykov V. A., Ladukhina N. R., Iagudin V. S., Arzamasova E. L., Gani S. V., Konstantinova N. I., Glotova G. A., Shipilova E. S., Krasnova S. G., Kachalov V. I., Stepanov A. N., Kharlamova K. E. (Current issues of pedagogy and psychology, 2025)
аbstract The chapter examines key aspects of development, socialization and psychological well-being of adolescents in the modern educational space. The role of the main factors of adolescent socialization is analyzed, including the role of family, school, peers and the digital environment. Particular attention is paid to the competencies of specialists working with adolescents, their ability to create a supportive environment for the formation of the adolescent's personality. Based on the conducted study of self-assessment of the competencies of specialists, strengths and development areas were identified, such as working with crisis states, the use of interactive methods and digital technologies. A model of interaction with adolescents based on the principles of trust, dialogue and action is proposed, as well as recommendations for improving the effectiveness of the specialist's professional activity.
Keywords: компетенции; социализация; образовательная среда; психологическое благополучие; подростковый возраст; educational environment; competencies; socialization; psychological well-being; adolescence